Prevalence of dementia in the Torres Strait. (10th November 2020) - Russell, Sarah G.; Quigley, Rachel; Thompson, Fintan; Sagigi, Betty; LoGiudice, Dina; Smith, Kate; Pachana, Nancy; Miller, Gavin; Strivens, Edward
Abstract: Objective: To examine the prevalence of dementia and problems associated with ageing in the Torres Strait. Methods: The study was conducted across all 18 island and 5 mainland communities in the Torres Strait and Northern Peninsula Area of Far North Queensland. Participants underwent a comprehensive health assessment and a Geriatrician assessment, which were used to establish consensus diagnoses. Results: A total of 276 Torres Strait residents aged between 45 and 93 participated in the study. The prevalence of dementia in the sample was 14.2%, which was 2.87 times higher than the wider Australian population. Conclusion: Torres Strait Islander peoples share the increased risk of dementia seen in Aboriginal Australians compared to the wider community. This highlights the need for interventions to address this increased dementia risk for Aboriginal and Torres Strait Islander communities.